Expression of variant von Willebrand factor (vWF) cDNA in heterologous cells: requirement of the pro-polypeptide in vWF multimer formation. - Verweij, C L (1987)
Von Willebrand factor (vWF) is a multimeric plasma glycoprotein synthesized by vascular endothelial cells as a pre-pro-polypeptide with a highly repetitive domain structure, symbolized by the formula: (H)-D1-D2-D'-D3-A1-A2-A3-D4-B1-B2-B3-C1-C2-(OH) A heterologous expression system for the synthesis of recombinant vWF protein was developed, consisting of a monkey kidney cell line (COS-1), transfected with full-length vWF cDNA. This system was shown to mimic the constitutive secretory pathway of vWF in endothelial cells, since dimerization and multimerization occur similarly. To determine whether the pro-polypeptide, composed of the domains D1 and D2, is involved in vWF multimerization, a vWF cDNA was constructed that lacked the coding sequence for the pro-polypeptide. The mutant vWF protein, expressed by COS-1 cells transfected with this cDNA, did not assemble beyond the dimer stage. From this observation, we conclude that (i) dimerization does not involve the pro-polypeptide of pro-vWF and (ii) the presence of the pro-polypeptide, as part of pro-vWF, is obligatory for multimerization. It is argued that the interactions, required for interchain binding, are mediated by the D domains.